Kinins Released by Erythrocytic Stages of Plasmodium falciparum Enhance Adhesion of Infected Erythrocytes to Endothelial Cells and Increase Blood Brain Barrier Permeability via Activation of Bradykinin Receptors - Silva, Leandro S.; Pinheiro, Alessandro S.; Teixeira, Douglas E.; Silva-Aguiar, Rodrigo P.; Peruchetti, Diogo B.; Scharfstein, Julio; Caruso-Neves, Celso; Pinheiro, Ana Acacia S. (Frontiers in Medicine, 2019)
Background. Plasmodium falciparum, the etiologic agent of malaria, is a major cause of infant death in Africa. Although research on the contact system has been revitalized by recent discoveries in the field of thrombosis, limited efforts were done to investigate the role of its proinflammatory arm, the kallikrein kinin system (KKS), in the pathogenesis of neglected parasitic diseases, such as malaria. Owing to the lack of animal models, the dynamics of central nervous system (CNS) pathology caused by the sequestration of erythrocytic stages of P. falciparum is not fully understood. Given the precedent that kinins destabilize the blood brain barrier (BBB) in ischemic stroke, here we sought to determine whether Plasmodium falciparum infected erythrocytes (Pf-iRBC) conditioned medium enhances parasite sequestration and impairs BBB integrity via activation of the kallikrein kinin system (KKS). Methods. Monolayers of human brain endothelial cell line (BMECs) are preincubated with the conditioned medium from Pf-iRBCs or RBCs (controls) in the presence or absence of HOE-140 or DALBK, antagonists of bradykinin receptor B2 (B2R) and bradykinin receptor B1 (B1R), respectively. Following washing, the treated monolayers are incubated with erythrocytes, infected or not with P. falciparum mature forms, to examine whether the above treatment (i) has impact on the adhesion of Pf-iRBC to BMEC monolayer (ii) increases the macromolecular permeability of the tracer BSA-FITC and (iii) modifies the staining pattern of junctional proteins (ZO-1 and β-catenin). Results. We found that kinins generated in the parasite conditioned medium, acting via bradykinin B2 and/or B1 receptors (i) enhanced Pf-iRBC adhesion to the endothelium monolayer and (ii) impaired the endothelial junctions formed by ZO-1 and β-catenin, consequently disrupting the integrity of the BBB. Conclusions. Our studies raise the possibility that therapeutic targeting of kinin forming enzymes and/or endothelial bradykinin receptors might reduce extent of Pf-iRBC sequestration and help to preserve BBB integrity in cerebral malaria (CM).